Tinjauan Bauran Pemasaran Dari Perspektif Pelaku Usaha Mikro - Riane Johnly Pio; Christoffel Kojo; Johny R. E. Tampi (JURNAL ADMINISTRASI BISNIS, 2022)
This training aims to provide an understanding of the marketing mix as a provision of knowledge for micro business actors in running a business. The training implementation uses an adult education approach such as interactive discussions by providing relevant and contextual illustrations in accordance with the factual problems faced by micro-enterprises. The training participants were 19 micro-enterprises with a sales turnover of between Rp. 150,000 to Rp. 500,000 per day. The training evaluation method was carried out by pre-test and post-test with analysis using descriptive statistics. The results of the training evaluation show that the majority of micro business groups run culinary businesses, but there are a small number who open stalls for daily basic needs. Understanding of the marketing mix increased by 42%, products increased by 10%, prices by 16%, place of business increased by 22%, and for promotion there was no change because the level of understanding was quite large, namely 89%. Through this activity, it is hoped that micro business actors in Ranotana Weru Village, Manado city can increase business and business sustainability.